Three-dimensional hollow CoS2 nanoframes fabricated by anion replacement and their enhanced pseudocapacitive performances. (20th June 2017) - Zeng, Xiaojun; Yang, Bai; Li, Xiaopan; Yu, Ronghai
Graphical abstract: Highlights: 3D hollow CoS2 nanoframes (HCSN) have been fabricated by anion replacement. 3D HCSN exhibit uniform broken hollow structure with large specific surface area. High specific capacitance and good cycling stability are obtained in these 3D HCSN. Abstract: Three-dimensional (3D) hollow CoS2 nanoframes (HCSN) have been fabricated by partial anion replacement of Co-based Prussian blue (PB) nanocubes. The initial self-assembled Co-based PB nanocubes can be converted to hollow Co3 [Fe(CN)6 ]2 nanostructures by corrosion reactions with thioacetamide (TAA) under suitable hydrothermal environment. The pure CoS2 are precipitated simultaneously on the surfaces of hollow Co3 [Fe(CN)6 ]2 nanostructures by ion replacement of [Fe(CN)6 ] 3− in Co-based PB nanocubes with S 2− in TAA to form the 3D HCSN. The as-synthesized 3D HCSN exhibit large specific surface area due to their uniform broken hollow structure with good dispersion, which results in their good electrochemical performances including a high specific capacitance of 568 F g −1 at 0.5 A g −1 and good cycling stability with 88.3% specific capacitance retention after 5000 cycles. The asymmetric supercapacitor made from the 3D HCSN can present a high energy density of 32.3 Wh kg −1 at a power density of 4 kW kg −1 . These 3D HCSN also shows good structural stability and low density, which further promotes their potential application in high-performance supercapacitors.